2016
DOI: 10.1016/j.jcat.2015.12.019
|View full text |Cite
|
Sign up to set email alerts
|

CO2 hydrogenation on Pt, Pt/SiO2 and Pt/TiO2: Importance of synergy between Pt and oxide support

Abstract: In the current study we combined density functional theory (DFT), kinetic Monte Carlo (KMC) simulations and experimental measurements to gain insight into the mechanisms of CO 2 conversion by hydrogen on the Pt nanoparticle (NP). The results show that in spite of the presence of active, low-coordinated sites, Pt NP alone is not able to catalyze the reaction due to the weak CO 2 binding on the catalyst. Once CO 2 is stabilized, the hydrogenation of CO 2 to CO via the reverse-water-gas shift (RWGS) reaction is p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
258
1
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 299 publications
(270 citation statements)
references
References 77 publications
(85 reference statements)
10
258
1
1
Order By: Relevance
“…Besides, CuÀ CeO 2 , FeÀ CeO 2 , and MnÀ CeO 2 catalysts maintained 100 % CO selectivity at the temperature 400°C. Pt was investigated in combination with TiO 2 or SiO 2 as a support by different researchers [90,91] where the supports promoted the overall CO 2 conversion, although the impact on the selectivity was rather small. To improve the Pt/TiO 2 catalytic impact on RWGS reaction Lee et al [92] investigated the effect of CeO 2 addition to a Pt/TiO 2 at temperature range 300-600°C.…”
Section: Rwgs Catalysts and Challengesmentioning
confidence: 99%
“…Besides, CuÀ CeO 2 , FeÀ CeO 2 , and MnÀ CeO 2 catalysts maintained 100 % CO selectivity at the temperature 400°C. Pt was investigated in combination with TiO 2 or SiO 2 as a support by different researchers [90,91] where the supports promoted the overall CO 2 conversion, although the impact on the selectivity was rather small. To improve the Pt/TiO 2 catalytic impact on RWGS reaction Lee et al [92] investigated the effect of CeO 2 addition to a Pt/TiO 2 at temperature range 300-600°C.…”
Section: Rwgs Catalysts and Challengesmentioning
confidence: 99%
“…On the Pt/SiO 2 interface, it is difficult to form oxygen vacancy, and CO 2 adsorption is weak. On the contrary, TiO 2 is a reducible carrier, on which oxygen vacancy can adsorb CO 2 strongly . It is reported that there are more oxygen vacancies in the (002) polar plane of ZnO, and there is a stronger interaction between Cu and ZnO with more (002) polar planes .…”
Section: Discussionmentioning
confidence: 99%
“…They The support plays an important role in CO 2 hydrogenation to CO through the RWGS reaction. Kattel et al prepared Pt, Pt/SiO 2 and Pt/TiO 2 materials as catalysts for the RWGS reaction [21], and showed that Pt nanoparticles alone cannot catalyze the RWGS reaction, while using SiO 2 and TiO 2 as support, the overall CO 2 conversion can be significantly improved, pointing towards a synergy effect between Pt and the oxide support. To reveal the synergy effect, they combined density functional theory (DFT), kinetic Monte Carlo (KMC) simulations and other experimental measurements.…”
Section: Heterogeneous Catalysismentioning
confidence: 99%